Pembangunan Hukum Siber Guna Pemanfaatan Ekonomi Berbasis Teknologi Informasi dalam Rangka Mewujudkan Ketahanan Nasional - Hassanain Haykal (Dialogia Iuridica, 2017)
This article aim to examine establishment of law in using Information Technology for economic goals which able to actualize nation security. This research is normative juridical research, uses secondary data consisting of primary, secondary and tertiary legal material. This article analyzed descriptively and used statute and conceptual approach. The result show that, establishment of cyber law is necessary as the result of the development of Information and Communication Technology, especially in economic activity of society. Development of cyber law also expected to raise standard of living in society, promote general welfare while maintaining and enforcing justice for all citizen. To achieve it, state must complete and establish law on economic utilization based on information and communication technology, upgrade the knowledge of legal expert and legislator comprehensively on technology for futuristic view, cultivate legal culture, and encourage the function of legislation.Â